Sliding mode controller for four leg shunt active power filter to eliminating zero sequence current, compensating harmonics and reactive power with fixed switching frequency - Chebabhi Ali; Fellah Mohammed-Karim; Benkhoris Mohamed-Fouad; Kessal Abdelhalim (Serbian Journal of Electrical Engineering, 2015)
In this paper, the four leg inverter controlled by the three dimensional space vector modulation (3D SVM) is used as the shunt active power filter (SAPF) for compensating the three phase four wire electrical network, by using the four leg inverter with 3D SVM advantages to eliminated zero sequence current, fixed switching frequency of inverter switches, and reduced switching losses. This four leg inverter is employed as shunt active power filter to minimizing harmonic currents, reducing magnitude of neutral wire current, eliminating zero sequence current caused by nonlinear single phase loads and compensating reactive power, and a nonlinear sliding mode control technique (SMC) is proposed for harmonic currents and DC bus voltage control to improve the performances of the three phase four wire four leg shunt active power filter based on Synchronous Reference Frame (SRF) theory in the dq0 axes, and to decoupling the four leg SAPF mathematical model.